Pengaruh Biaya Pengendalian Kualitas Dan Biaya Persediaan Terhadap Volume Produksi: (Studi Kasus Pada Perusahaan Kacang Telor Bebe Di Tasikmalaya) - Alma Fairuzia Annur (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
Every company wants a quality product because this will reflect the company's success in meeting consumer expectations. In addition, inventory must be able to allocate asset requirements fairly and at low cost. Both of these facts are related to the company production Kacang Telor Bebe . The research sample used is data on quality control costs, inventory costs and production volumes for 30 months. Data analysis method using classical assumption test, multiple linear regression, correlation analysis, coefficient of determination and hypothesis testing. Based on the results of data analysis, the cost of quality control proved to have a negative effect on the volume of production. While the variable cost of inventory proved to have a positive effect on the volume of production.